Prevalence and characteristics of polycystic ovary syndrome in Brazilian women: protocol for a nation-wide case–control study. Issue 10 (22nd October 2019) - Spritzer, Poli Mara; Marchesan, Lucas B; Santos, Betânia R; Cureau, Felipe V; Oppermann, Karen; Reis, Rosana Maria dos; Ferriani, Rui A; Weiss, Rita; Meirelles, Ricardo; Candido, Ana Lucia; Reis, Fernando M
Abstract : Introduction: Brazil is a large country, with a population of mixed ethnic background and broad variation in dietary and physical activity traits across its five main regions. Because data on Brazilian women with polycystic ovary syndrome (PCOS) are still scarce, a nation-wide collaborative study was designed to determine the prevalence of metabolic and reproductive abnormalities and the presence of anxiety and depression in Brazilian women with PCOS. In addition, the study aims at describing how these characteristics are distributed across PCOS phenotypes and at detecting associations with regional demographic and lifestyle aspects, genetic variants, and epigenetic markers. Methods and analysis: The Brazilian PCOS study is being conducted in the outpatient clinics of eight university hospitals within the public healthcare network (Unified Health System) across the country. Additional centres will be included following completion of the research ethics approval process. The sample includes women with PCOS according to Rotterdam criteria at inclusion in the study and a control group of healthy women matched by age, socioeconomic status and geographical region. Data will be collected in each centre and incorporated into a unified cloud database. Clinical, demographic, socioeconomic, psychological, metabolic, epigenetic and genotypic variables will be evaluated. The data resulting from this study will be useful to guide specific public strategies for primary and secondary prevention of metabolic and reproductive comorbidities in the PCOS population of Brazil. Ethics and dissemination: The study protocol was approved by each local Research Ethics Committee. Written informed consent will be obtained from each participant. During data collection, analysis and publication, care will be taken to ensure confidentiality of participant information. Study results will be published in peer-reviewed journals and disseminated at international conferences. This research protocol was registered with the Research Ethics Committee of HCPA, through Plataforma Brasil. Trial registration number: CAAE 18082413.9.1001.5327